An improved method for qPCR detection of three Phytophthora spp. in forest and woodland soils in northern Britain. Issue 6 (28th October 2015) - Elliot, M.; Schlenzig, A.; Harris, C. M.; Meagher, T. R.; Green, S.
Summary: Using TaqMan qPCR assays, DNA of P. ramorum, P. kernoviae and P. austrocedri was detected in 500 g soil samples collected from twelve infected forest and woodland sites in northern Britain. Phytophthora DNA was also amplified in soil adhering to boots after walking transects along footpaths or animal trails. At two sites, Phytophthora DNA was detected in soil over a 4‐year period following removal of infected hosts. This new method enabling assessment of larger quantities of soil demonstrates the contamination risk of these pathogens in soil at infected sites and improves our understanding of the mechanisms of persistence and spread.